IMPROVING STUDENTS’ SKILL IN WRITING DESCRIPTIVE TEXTS THROUGH PERSONAL PHOTOGRAPH MEDIA TO THE TWELFTH GRADE STUDENTS OF SMA SWASTA PELITA NUSANTARA LAWE SIGALA-GALAIN THE ACADEMIC YEAR OF 2020/2021 - N, Niawanti; Sembiring, Novalina; Sari, Anna Stasya Prima (Kairos English Language Teaching Journal, 2021)
This research was primarily conducted to prove that the application of Personal Photograph media could improve the writing skill of the twelfth grade students of SMA Swasta Pelita Nusantara Lawe Sigala-gala in the academic year of 2020/2021 and to describe their responses towards the application of Personal Photograph media in the processes of learning writing skill. Each cycle consisted of four meetings. The quantitative data analysis showed that the students mean score increased continually from 57,31 with 9% passing Minimum Mastery Criteria in pre-test, 71,81 with 36% Minimum Mastery Criteria in formative-test, 83,31 with 82% Minimum Mastery Criteriain post-test. The qualitative data analysis showed that the students’ responses after being taught through the application of Personal Photograph media are very good. The result is most of the students gave good responses to the Personal Photograph media which was used in learning teaching process. It is suggested that teachers use Personal Photograph media as an alternative in writing descriptive texts to the students in Senior High School in order to improve their students’ writing skill, particularly in writing descriptive texts.